Fitnesser’s Intrinsic Motivations of Green Eating: An Integration of Theory of Planned Behavior and Hedonic-Motivation System Adoption Model - Chen, Yuan; Lee, Bey-Fen; Lu, Yen-Cheng (Frontiers in Psychology, 2021)
Global climate change arouses people's attention to environmental protection and therefore changes consumption habits. Food overconsumption not only produces extra waste but also pollutes the environment. Therefore, it is important to understand the factors that motivates people to eat green, an eco-friendly way to consume food. To keep the body in good shapes, the fitnessers concern more about the diet than the general people. This study explored intrinsic motivations, such as social recognition, environmental ethics, curiosity, joy of purchase, perceived usefulness, subjective norm, and perceived behavior control as constructs that affect fitnesser’s green eating intention. All constructs except curiosity have significant impacts on behavior intention. The results demonstrate that social recognition and environmental ethics have significant effects on curiosity, joy of purchase, perceived usefulness, subjective norm, and perceived behavior control. The mediation effects between social recognition and behavior intention is not supported. The mediator between environmental ethics and behavior intention are joy of purchase, perceived usefulness, subjective norm, and perceived behavior control.